Safety and Efficacy of Coils in Conjunction With the Pipeline Flex Embolization Device for the Treatment of Cerebral Aneurysms - Zhang, Qianqian; Shao, Qiuji; Chang, Kaitao; Zhang, Hongyun; He, Yingkun; Andrade-Barazarte, Hugo; Sheng, Zhiyuan; Mo, Xiao; Zemmar, Ajmal; Li, Li; Li, Tianxiao (Frontiers in Neurology, 2021)
Abstract Background: Flow diverters (FD) have shown promising results in the treatment of intracranial aneurysms (IAs). However, there is still controversy whether pipeline flex embolization device (PED flex) assisted coils can facilitate the curing of aneurysms. Our aim was to assess the safety and effectiveness of PED flex adjunctive with coils (PED flex +coil) in the treatment of IAs. Method：Patients who underwent PED flex treatment in combination with coiling between January 2018 and June 2020 were included in this study. Clinical and radiographic characteristics before and after treatments were retrospectively evaluated. The study cohort comprised of 125 patients with 140 IAs, which was subdivided into two subgroups: one group included patients treated only through PED alone, and the other group included patients treated through PED flex adjunctive with coil. Patients baseline characteristics, aneurysm characteristics, treatment-related factors, and outcomes were analyzed to determine the effectiveness of both techniques. Results: Aneurysms in the PED flex +coil group were larger (10.0±5.8 mm, P <0.001, Table 2) and wider (7.2±4.6 mm, P =0.002, Table 2) compared with those in the PED flex group. There was no statistical difference in the perioperative complications rate between two groups. The overall complete occlusion rate was 75.7% at 6.2 months, with 71.7% at 6.2 ±1.7 months in the PED flex group and 85.4% at 6.2 ±1.8 months in the PED flex +coil group, respectively. Higher percentage of satisfactory angiography results were found in the PED flex +coil group during follow-up (92.7% vs 78.8%, P =0.047, Table 3). Conclusion: PED flex placement with adjunctive coil embolization represents a safe alternative option for the treatment of IAs. In these cases, coils embolization increases the occlusion rate in PED flex treated patients without increasing periprocedural complications.